2006
DOI: 10.1016/j.jvs.2006.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of embolization protection device-specific technical difficulties during carotid artery stenting

Abstract: During CAS, both balloon occlusion and filter devices provide acceptable results and appear complimentary. Filters can be used preferentially to avoid a 10% incidence of reversible neurologic compromise associated with balloon occlusion, except in critically narrowed or tortuous lesions when balloon occlusion may be preferred because of a 12% need for unprotected predilatation with filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…[245][246][247][248][249][250][251] If properly deployed, an EPD can reduce the neurological risks associated with CAS, but these devices may also be associated with failures. 53,196,198,247,[252][253][254][255][256][257][258] Among the general risks is access-site injury, which complicates 5% of cases, but most such injuries involve pain and hematoma formation and are self-limited. [259][260][261][262] Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%
“…[245][246][247][248][249][250][251] If properly deployed, an EPD can reduce the neurological risks associated with CAS, but these devices may also be associated with failures. 53,196,198,247,[252][253][254][255][256][257][258] Among the general risks is access-site injury, which complicates 5% of cases, but most such injuries involve pain and hematoma formation and are self-limited. [259][260][261][262] Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%
“…Distal embolism is always a feared complication during endovascular procedures in carotid arteries (2,10,16). This high propensity for embolic plaque debris led to the development of distal protection techniques to be used during endovascular procedures performed for lesions of the carotid bifurcation (12,13,15).…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of balloon and filter embolic protection devices during CAS found transient neurologic compromise occurred in 10% of the balloon group and identified no anatomic-specific predictors of balloon occlusion intolerance. 8) In another study of cerebral ischemia with PercuSurge balloon occlusion during CAS, an incomplete circle of Willis or contralateral carotid artery occlusion, or both, was present in 8 of 10 patients in whom neurologic intolerance developed during occlusion of carotid artery. 1) In other words, however, 2 of 10 patient developed transient neurologic symptoms with PercuSurge balloon occlusion during CAS in spite of their expected sufficient collateral circulation.…”
Section: Discussionmentioning
confidence: 97%